The electronic management applications in Algerian public institutions The National Center for Commercial Register as a Model - Mostapha, Bouchentouf Moulay; Talhi, Hichem (The journal of contemporary issues in business and government, 2023)
This study aims to highlight the implementation of electronic administration within the Algerian public institutions, following a significant period of Algeria’s adoption of the electronic administration project. The latter leads to the embedment of information and communication technologies into the electronic practices, in the dealings of several local administrations with the citizens, and replaces the old applications with modern ones. The case study for this research is the National Center for Commercial Register. The most important findings of this topic are: the Algerian administration has accomplished a significant milestone in transforming into "zero paper administration" thanks to the well-planned governmental program involving the modernization and digitization of several public sectors and administrations. In this respect, the National Center for Commercial Register administration has also followed this new path through the adoption of the electronic administration applications, and this is via the creation of the electronic portal "Sidjilcom" and the implementation of the electronic commercial register model "E.C.R".